2016
DOI: 10.1038/tp.2015.208
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis identifies genetic variations in subjects with myalgic encephalomyelitis/chronic fatigue syndrome

Abstract: Myalgic encephalomyelitis, also known as chronic fatigue syndrome or ME/CFS, is a multifactorial and debilitating disease that has an impact on over 4 million people in the United States alone. The pathogenesis of ME/CFS remains largely unknown; however, a genetic predisposition has been suggested. In the present study, we used a DNA single-nucleotide polymorphism (SNP) chip representing over 906,600 known SNPs to analyze DNA from ME/CFS subjects and healthy controls. To the best of our knowledge, this study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 59 publications
1
62
2
Order By: Relevance
“…Generalized gene-set analysis of the SNP data in MAGMA did not identify any gene-set 344 significantly enriched in either our data, or the data from Schlauch et al (2016). 345 346 Characterisation of SNP rs11712777 347 We used a variety of online reference resources to characterize the current knowledge of 348 rs11712777, and how it may influence ME/CFS phenotype (see Methods section).…”
Section: Introductionmentioning
confidence: 95%
“…Generalized gene-set analysis of the SNP data in MAGMA did not identify any gene-set 344 significantly enriched in either our data, or the data from Schlauch et al (2016). 345 346 Characterisation of SNP rs11712777 347 We used a variety of online reference resources to characterize the current knowledge of 348 rs11712777, and how it may influence ME/CFS phenotype (see Methods section).…”
Section: Introductionmentioning
confidence: 95%
“…Mice from two N ‐ethyl‐ N ‐nitrosourea (ENU) lines show abnormal, low amplitude voluntary wheel‐running activity patterns. Circadian activity patterns are double plotted for ease of visualization, with each horizontal line representing 48 hours and successive days plotted along the Y‐axis. Wheel revolutions are depicted as black marks on the horizontal lines.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in several genes (eg, the adrenergic receptor a1 ( ADRA1A ), the serotonin transporter ( SLC6A4 ) or receptor ( HTR2A ), tyrosine hydroxylase ( TH ), corticosteroid‐binding globulin ( CBG ), corticotropin releasing hormone receptor 1 ( CRHR1 ), the cytokine IL‐1B, neuronal PAS domain protein 2 ( NPAS2 ), the nuclear receptor subfamily 3; group C, member 1 glucocorticoid receptor ( NR3C1 ) and the glutamate receptor‐ionotropic kinase 2 ( GRIK2 ) have all been linked to either the occurrence or the severity of fatigue symptomology in humans . Furthermore, a recent study comparing CFS patients to healthy controls identified 442 additional candidate genes associated with CFS . In addition, mice with mutations in several genes have shown phenotypes consistent with fatigue (eg, corticosteroid‐binding globulin ( Cbg ), recombinase activating gene 2 ( Rag2 ) and interleukin‐10 ( Il10 )) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3; group C, member 1 glucocorticoid receptor (NR3C1), and the glutamate receptor -69 ionotropic kinase 2 (GRIK2)) have been linked to both the occurrence and severity of 70 fatigue symptomology (24)(25)(26)(27)(28)(29)(30). A study comparing chronic fatigue syndrome patients to 71 healthy controls using a single nucleotide polymorphism (SNP) chip with over 900, 000 72 SNPs identified 442 candidates associated with chronic fatigue syndrome, and 73 highlighted two genes never before associated with fatigue (C-type lectin domain family 74 4, member M (CLEC4M) and coiled-coil domain containing 157 protein (CCDC157)) 75 (31). In addition, mice with mutations in several genes have shown phenotypes 76 consistent with fatigue (e.g., corticosteroid-binding globulin (CBG), recombinase 77 activating gene 2 (RAG2), and interleukin-10 (IL-10)) (32)(33)(34).…”
Section: Phase 62mentioning
confidence: 99%